The Effects of Interferons on Allogeneic T Cell Response in GVHD: The Multifaced Biology and Epigenetic Regulations - Zhao, Chenchen; Zhang, Yi; Zheng, Hong (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative therapy for hematological malignancies. This beneficial effect is derived mainly from graft-versus-leukemia (GVL) effects mediated by alloreactive T cells. However, these alloreactive T cells can also induce graft-versus-host disease (GVHD), a life-threatening complication after allo-HSCT. Significant progress has been made in the dissociation of GVL effects from GVHD by modulating alloreactive T cell immunity. However, many factors may influence alloreactive T cell responses in the host undergoing allo-HSCT, including the interaction of alloreactive T cells with both donor and recipient hematopoietic cells and host non-hematopoietic tissues, cytokines, chemokines and inflammatory mediators. Interferons (IFNs), including type I IFNs and IFN-γ, primarily produced by monocytes, dendritic cells and T cells, play essential roles in regulating alloreactive T cell differentiation and function. Many studies have shown pleiotropic effects of IFNs on allogeneic T cell responses during GVH reaction. Epigenetic mechanisms, such as DNA methylation and histone modifications, are important to regulate IFNs’ production and function during GVHD. In this review, we discuss recent findings from preclinical models and clinical studies that characterize T cell responses regulated by IFNs and epigenetic mechanisms, and further discuss pharmacological approaches that modulate epigenetic effects in the setting of allo-HSCT.